Performance in organic chemistry at either a four-year university or community college predicts academic performance in an accelerated school of pharmacy - Smith, Troy J.; Ross, Jason; Breese, Charles R.; Burmeister, Melissa A. (Frontiers in Education, 2025)
PharmD programs face the growing challenge of students matriculating with a lack of academic preparedness, particularly in the foundational sciences. One key component of pharmacy is organic chemistry. Here, we determined if the setting of where undergraduate organic chemistry coursework is taken [i.e., 4-year university (U) vs. community college (CC)], is associated with varied academic outcomes in an accelerated Doctor of Pharmacy program. Five student cohorts representing a total of 180 graduates were analyzed. Graduates were first divided into those who studied undergraduate organic chemistry I and II at a U vs. CC and the pharmacy year 1 (PY1) and pharmacy year 2 (PY2) grade point averages (GPAs) compared. Students were then dichotomized into two subcategories based on whether they received an above average (i.e., A or B) or average (i.e., C) grade in organic chemistry I or II. Linear regression analysis was performed to determine whether performance in undergraduate organic chemistry is associated with programmatic GPA. PY1 and PY2 GPAs reflecting the didactic curriculum did not differ between students who took organic chemistry I and II at a U vs. C. The grade distributions in both organic chemistry I and II differed between U vs. CC, with more average grades received at a U. Institution type was not associated with differences in GPA outcomes. However, average performance in organic chemistry I was associated with lower PY1 and PY2 GPAs. Taken together, admissions committees should consider using performance in undergraduate organic chemistry I when evaluating an applicant’s academic readiness.